Kedudukan, Hak dan Kewajiban Ibu dalam Perspektif Islam - Zurifah Nurdin (Institut Agama Islam Negeri Bengkulu, 2015)
God created creatures called Umm, the Indonesian people call with a call mom, mother, ummi, mama, and so forth. The phrase was only given to women who become and serve someone who is highly respected and cherished because they are given the responsibility by Allah to pregnancy, childbirth, breastfeeding, and also education. Dignity of a mother is very high compared to the other. A heavy resposibility in the form of right and obligations of the mother is what should be understood. So that a child can position the mother in the correct position and is more than the father. It has been explained that the mother is the women who gave bisrt. Therefore the position of the mother is high and mother very broad meaning very large so it's natural rights are required to worship him.